Anaemia in early childhood pneumonia ? prevalence, predictors, and associated growth in the Drakenstein child health study (DCHS) - Prentice, Carley (Department of Public Health and Family Medicine, 2024)
Background: Concurrent anaemia and pneumonia in under-fives living in LMICs is a complex relationship associated with high morbidity and mortality. Ascertaining whether there is an increased prevalence of anaemia among pneumonia infected under-fives can provide valuable insights for more effective treatments. Additionally, highlighting individual and maternal risk factors of anaemia as well as associated adverse growth outcomes among under-fives can bring about findings to prioritise resource allocation for anaemia prevention and treatment. Methods: This cross-sectional sub-study analysed data from the Drakenstein Child Health Study (DCHS), a South African population-based birth cohort which enrolled pregnant women. Mother-child pairs were followed prospectively, and a subgroup of children had additional data collected (including haemoglobin (g/dL) measurements) during episodes of LRTI/pneumonia. Prevalence ratios were used to assess the impact of LRTI/pneumonia severity on anaemia status. Binary logistic regression models were used to analyze the effects of predictors on risk of child anaemia and linear regression models were used to analyze the effect of anaemia on adverse growth outcomes (WAZ and HAZ). Results: 28% of first LRTI/pneumonia episodes co-occurred with anaemia (95% CI, 24.9 - 31.8), and median child age was 8.4 months during the episode. When all LRTI/pneumonia episodes were included, anaemia prevalence was higher among under-fives treated in hospital compared to those treated in ambulatory care (38.9% compared to 30.3% respectively, p=0.04). Additionally, children who experienced recurrent LRTI/pneumonia (2+ episodes) were 1.28 times as likely to have anaemia compared to children experiencing a first episode (95% CI, 1.03 - 1.59, p=0.023). Overall, children aged 6-59 months, with low socioeconomic status, and were exclusively breastfed for more than 1 month were strongly associated with anaemia (p<0.05). Children with concurrent LRTI/pneumonia and anaemia were found to be at increased risk of wasting (WAZ) and decreased risk of stunting (HAZ). Conclusions: This study provides evidence of a high prevalence of concurrent LRTI/pneumonia and anaemia among under-fives in South Africa. It demonstrates the complex interplay between these conditions and various risk factors including older child age, maternal anaemia, exclusive breastfeeding, low socioeconomic status, and food insecurity. These findings highlight the need for multi-sectoral approaches to address the medical treatment and underlying social determinants of health that contribute to the burden of LRTI/pneumonia and anaemia in under-fives.